NOTAS CRÍTICAS A IFIGENIA EN ÀULIDE - Calderón Dorda, Esteban (Myrtia, 2001)
The present work consists of several notes on the text of Euripides’ Iphigeneia in Aulis (22, 77-78, 447-449, 521, 657, 665, 717, 749-750, 1017-1018, 1177-1179, 1185, 1207-1208, 1380-1382, 1443, 1494).